Islamic philosophy of religion essays from analytic perspectives - Zarepour, Mohammad Saleh ca. 20./21. Jh (Routledge, 2024)
This volume focuses on Islamic philosophy of religion with a range of contributions from analytic perspectives. It opens with methodological discussions on the relationship between the history of Islamic philosophy and contemporary analytic philosophy. The book then offers a philosophical examination of some specific Islamic beliefs as well as some approaches to general beliefs that Islam shares with other religions. The chapters address a variety of topics from the existence and attributes of God through to debates on science and religion. The authors are predominantly scholars from Muslim backgrounds who tackle philosophical issues concerning Islam as their own living religion, representing internal perspectives that have never been vocal in analytic philosophy of religion so far. This is valuable reading for scholars and students of philosophy, theology, and religious studies
Introduction; Mohammad Saleh Zarepour; PART I Methodology; 1 What Can Contemporary Analytic Philosophy Do for the Historians of Islamic Philosophy?; Sajjad Rizvi; 2 What Can the History of Islamic Philosophy Do for Contemporary Analytic Philosophers?; Anthony Booth; PART II Existence and Uniqueness of God; 3 Kalam and Cognition; Mahrad Almotahari; 4 God’s Existence and the Uniqueness Claim; Nazif Muhtaroglu; PART III: Attributes of God; 5 Divine Power and Divine Knowledge; Edward Omar Moad; 6 The Doctrine of Divine Simplicity Considered in Light of Averroes’s Conception of Divine Knowledge; Bakinaz Abdalla; PART IV: Miracles; 7 The Metaphysics of Miracles: Avicenna on Natures and Prophetic Powers; Emann Allebban; 8 Of Miracle of Miracles: An Introduction to the Qur’anic View of Miracle; Rouzbeh Touserkani; PART V: Faith and Its Obstacles; 9 Faith, Knowledge, and Certainty: An Islamic Philosophy Perspective; Hamid Vahid; 10 Islam and The Problem of Divine Hiddenness; Imran Aijaz; 11 An Analysis of Some Problems of Evil from an Islamic Perspective; Hajj Muhammad Legenhausen; PART VI: Ethics and Morality; 12 Islamic Philosophers' Idea of Heaven: A Moral Analysis; Amir Saemi; 13 Towards Epistemic Justice in Islam; Fatema Amijee; PART VII: Science and Religion; 14 Adam, Eve, and Human Evolution: Is There a Conflict?; Shoaib Ahmed Malik; 15 Islamic Occasionalism within the context of Modern Religion and Science Debate; Ozgur Koca
Keywords: bicssc / Philosophy of religion; bicssc / Islamic theology; bisacsh / RELIGION / Islam / General; Islamische Philosophie; Religionsphilosophie; Analytische Philosophie; Aufsatzsammlung